2013
DOI: 10.1007/s11999-012-2596-9
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 Chitranjan Ranawat Award: Intraarticular Analgesia After TKA Reduces Pain: A Randomized, Double-blinded, Placebo-controlled, Prospective Study

Abstract: Background Postoperative pain after total knee arthroplasty remains one of the most important challenges facing patients undergoing this surgery. Providing a balance of adequate analgesia while limiting the functional impact of regional anesthesia and minimizing opioid side effects is critical to minimize adverse events and improve patient satisfaction. Questions/Purposes We asked whether bupivacaine delivered through an elastomeric device decreases the (1) patients' perception of pain after TKA; (2) narcotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…YaDeau et al [48] reported decreased postoperative cognitive dysfunction in patients who received a single-shot femoral nerve block immediately before TKA (2.5% versus 0%), while Marino et al [34] found decreased postoperative cognitive dysfunction with the use of continuous lumbar or femoral block as compared to IV PCA alone (0%, 1.3%, and 10.7%, respectively). In contrast, intraarticular infusion of bupivacaine after TKA was not found to change the incidence of postoperative cognitive dysfunction as compared to placebo [15]. When narcotic medications were used, morphine and meperidine appeared to be associated with an increased risk of postoperative cognitive dysfunction, irrespective of the mode of administration (IV, intramuscular [IM], or epidural).…”
Section: Multimodal Anesthetic Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…YaDeau et al [48] reported decreased postoperative cognitive dysfunction in patients who received a single-shot femoral nerve block immediately before TKA (2.5% versus 0%), while Marino et al [34] found decreased postoperative cognitive dysfunction with the use of continuous lumbar or femoral block as compared to IV PCA alone (0%, 1.3%, and 10.7%, respectively). In contrast, intraarticular infusion of bupivacaine after TKA was not found to change the incidence of postoperative cognitive dysfunction as compared to placebo [15]. When narcotic medications were used, morphine and meperidine appeared to be associated with an increased risk of postoperative cognitive dysfunction, irrespective of the mode of administration (IV, intramuscular [IM], or epidural).…”
Section: Multimodal Anesthetic Techniquesmentioning
confidence: 98%
“…However, of those studies, only nine of 21 (43%) explicitly reported blinding of patients, clinicians, and/or assessors to the participants' treatment arm allocation [4,12,15,20,24,27,29,47,48]. Only nine of 21 (43%) reported performing an a priori power calculation for the outcome of postoperative cognitive dysfunction [4,16,24,27,29,34,38,39,48], with one of these studies failing to recruit a sufficient number of patients [38].…”
Section: Study Designs and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile bearing TKA [16], sex-specific TKA [6], high-flexion TKA [40,55], and refinements in the design of cruciate-retaining (CR) and posterior-stabilized (PS) TKA [4,14,33,64] have all been introduced in recent years. In addition, improvements in perioperative management, including more limited incisions [62] and multimodal pain management [23,44], have been instituted to speed the recovery process and potentially improve the ultimate patient outcome and satisfaction with TKA.…”
Section: Introductionmentioning
confidence: 99%
“…From these we identified 12 eligible RCTs. [3][4][5][6][7][8][9][10][11][12][13][14] Inter-observer agreement for trial eligibility was good (kappa = 0.75; SE 0.053). Table I reports the characteristics of the included trials and the local anaesthetic protocols used in the trials.…”
Section: Trial Identification and Selectionmentioning
confidence: 95%